Bacterial Endosymbiont Localization in Hyalesthes obsoletus, the Insect Vector of Bois Noir in Vitis vinifera - Gonella, Elena (American Society for Microbiology (ASM), 2011)
One emerging disease of grapevine in Europe is Bois noir (BN), a phytoplasmosis caused by “Candidatus Phytoplasma solani” and spread in vineyards by the planthopper Hyalesthes obsoletus (Hemiptera: Cixiidae). Here we present the first full characterization of the bacterial community of this important disease vector collected from BN-contaminated areas in Piedmont, Italy. Length heterogeneity PCR and denaturing gradient gel electrophoresis analysis targeting the 16S rRNA gene revealed the presence of a number of bacteria stably associated with the insect vector. In particular, symbiotic bacteria detected by PCR with high infection rates in adult individuals fell within the “Candidatus Sulcia muelleri” cluster in the Bacteroidetes and in the “Candidatus Purcelliella pentastirinorum” group in the Gammaproteobacteria, both previously identified in different leafhoppers and planthoppers. A high infection rate (81%) was also shown for another symbiont belonging to the Betaproteobacteria, designated the HO1-V symbiont. Because of the low level of 16S rRNA gene identity (80%) with the closest relative, an uncharacterized symbiont of the tick Haemaphysalis longicornis, we propose the new name “Candidatus Vidania fulgoroideae.” Other bacterial endosymbionts identified in H. obsoletus were related to the intracellular bacteria Wolbachia pipientis, Rickettsia sp., and “Candidatus Cardinium hertigii.” Fluorescent in situ hybridization coupled with confocal laser scanning microscopy and transmission electron microscopy showed that these bacteria are localized in the gut, testicles, and oocytes. As “Ca. Sulcia” is usually reported in association with other symbiotic bacteria, we propose that in H. obsoletus, it may occur in a bipartite or even tripartite relationship between “Ca. Sulcia” and “Ca. Purcelliella,” “Ca. Vidania,” or both.